PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP JUMLAH SEL NEURON DI CEREBELLUM Rattus norvegicus BARU LAHIR - Herlina Alvianti N (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 1970)
Efforts could be made to improvehuman resources that have intelligencerequired a positive relationship betweenhealth and good education quality, one of theefforts to improve human resources requiresgood brain quality since the phase ofconception. Classical music has been shownto boost brain function and human intellectualoptimally believed to have the best stimulatingeffect on babies. Cellular exposure to Mozartaffects the number of more neuronal cells.Analyze the number of cerebrum andcerebellum neuronal cells of newborn Rattusnorvegicus between the exposed to Mozartmusic, Beethoven, Chopin and not exposed tomusic during pregnancy. This research wasan experimental research with posttest onlycontrol group design. The sample was dividedinto four groups randomly, non-exposed,Mozart music exposure group, Beethovenmusic exposure group, Chopin musicexposure group, exposed for 1 hour during thenight after Rattus norvegicus was pregnant onday-10 with an intensity of 65 dB and adistance of 37 cm from the rat cage. On the20th day of the pregnant mother of Rattusnorvegicus was sacrificed and selected two ofRattus norvegicus's babies with the greatestweight and then the brains of Rattusnorvegicus's babies were decapitated andbrain dissection to count the number ofneuronal cells with Hemotoxyln-Eosinstaining. The statistical results showed thatthe number of neurons of cerebellum cells inthe Mozart group differed significantly fromBeethoven, Chopin and not exposed to musicwith p <0.05. The number of neuronal cells ofcerebellum of the newborn Rattus norvegicuswho exposed to Mozart music duringpregnancy proved higher than that exposed toBeethoven music, Chopin and not exposed tomusic.